Role Of Vitamins In Cardiovascular System - A Review - Hafiz Syed Mohammad Osama Jafri; Saeeda Baig; Sabra Siraj (ziauddin University, 2022)
Cardiovascular disease (CVD), the leading cause of mortality around the world, among many risk factors has but some are modifiable one of which is lifestyle. The key element in the healthy lifestyle is diet that boosts cardiovascular health, especially few key vitamins which have been found to help the heart and blood vessels working properly. Vitamins, especially those with antioxidant potency, may have a role in the prevention of and therapy for CVD. Antioxidant vitamins such as vitamin C, vitamin E, and carotenoids are able to decrease the rate of oxidative stress, which may have a principal role in the pathogenesis of atherosclerosis and CVD. Vitamin D also contributes to the maintenance of cardiovascular health and can induce cardio protective effects. Although most of the randomized controlled trials on vitamins failed to show the benefit of vitamin supplementation for cardiovascular outcomes, a number of observational and cohort studies, meta-analyses, and stratified analyses of large vitamin trials appeared to show an effect in some aspects of cardiovascular prevention. Moreover, many of the vitamin trials for secondary prevention are biased by use of vitamins and drugs effective for cardiovascular prevention; therefore, the conclusions drawn from them supporting the effectiveness of vitamin substitution for the prevention of CVD may be inappropriate. This review summarizes the available data suggesting the role of few vitamins in cardiovascular health and in the primary prevention of CVD; also, examining the use of new concepts and new study designs to establish the effectiveness of vitamin supplementation in the therapy for and prevention of CVD. breast masses.